Comparação entre baixas doses de herbicida à base de Glifosato e seu princípio ativo na função renal de ratos - Nacano, Bruno Reis Moreira (2020)
A fatal epidemic qualified for chronic kidney disease (DRC) is responsible for the deaths of thousands of people in Central America, Sri Lanka and India. It is known as “chronic kidney disease of unknown etiology” (CKD). Glyphosate-based herbicides (HBG), the most used in the world, have been used as the main cause of disease. The aim of this study was to analyze the effect of glyphosate and HBG on kidney function in rats. Wistar rats were divided into three groups: Control Group, submitted to the inoculation of buffer solution; Glyphosate Group and HBG Group, which were submitted to 5 mg / kg of glyphosate or HBG weight, once a day, for up to 30 days. Blood and urine samples were collected 24 hours to determine urea and plasma creatinine, creatinine clearance and lipid peroxidation. The animals were killed and removed for histological analysis by KIM-1 immunohistochemistry. There was an increase in creatinine clearance, and a decrease in creatinine and urea levels in the countries of the HBG group, suggesting hyperfiltration. Histological statistics show vacuolization and increased KIM-1 labeling in tubular cells, especially in the HBG group. However, a lipid peroxidation in the urine was observed only in the Glyphosate group. Both groups showed a significant difference in renal mass, but there was no significant difference in body weight, despite a trend. Our results demonstrate that HBG, plus Glyphosate, affects kidney function at low doses. The effects of HBG on kidney function are possibly due to inert substances having no herbicide, or just indicating further studies on the effect of glyphosate-based herbicides.